Cholestasis and Acute Cholecystitis in Hyperthyroidism Treated With Methimazole - Wei-Che Chen; Zheng-Xin Zhu; Chao-Hung Wang; Ming-Nan Chien (International Journal of Gerontology, 2009)
Hepatic dysfunction and jaundice are usually present in patients with hyperthyroidism. It may be the clinical manifestation of the disease or the adverse effect of antithyroid therapy. We report a 69-year-old male with hyperthyroidism who developed cholestasis and acute cholecystitis after a 4-day course of methimazole. After withdrawal of methimazole, his cholestasis subsided.